Hadith #149 - Sahih Muslim - Safinah (Sahih Muslim)
A hadith like this as narrated by Ibn ‘Umar has also been transmitted by Abu Sa’id al-Khudri.
Grade: Sahih

Hadith #643 - Sahih Muslim - Safinah (Sahih Muslim)
The Messenger of Allah (ﷺ) took a bath with one Sa` of water because of sexual intercourse and performed ablution with one Mudd.
Grade: Sahih

Hadith #644 - Sahih Muslim - Safinah (Sahih Muslim)
The Messenger of Allah (ﷺ) took a bath with one Sa’ of water and performed ablution with one Mudd (of water) ; and in the hadith narrated by Ibn Hujr the words are: One Mudd sufficed for his (Holy Prophet’s) ablution. And Ibn Hujr said that (his Shaikh) Isma’il was much advanced in age, and it was because of this that he could not fully rely on him for this tradition.
Grade: Sahih